Practices and perception of Nigerian community pharmacists towards antimicrobial stewardship program - Abubakar, Usman (Innovare Academic Sciences Pvt Ltd, 2020)
ABSTRACT Objective: Community pharmacists have an important role in promoting the appropriate use of antibiotics. There is a paucity of data describing the contributions of community pharmacists in antimicrobial stewardship program (ASP) in Nigeria. This study evaluated the practices and perceptions of community pharmacists towards ASP. Methods: This was a cross-sectional study conducted among community pharmacists in two cities in Northern Nigeria: Minna and Kaduna, using a 30-item validated and pre-tested questionnaire. Data collected between April and May 2019 and analyzed using SPSS version 23. Results: Of 130 community pharmacists, 98 completed and returned the questionnaire (response rate: 75.3%). More than 90% strongly agreed/agreed that ASP is important to reduce inappropriate use of antibiotics and antibiotic resistance, improve patient’s clinical outcomes. However, lack of training (56.1%), lack of cooperation from physicians (61.2%) and lack of access to patient records (66.8%) were identified as barriers to community pharmacists’ involvement in ASP. Overall, community pharmacists had good practices (median score: 3.5; IQR: 1–5) and positive perceptions (median score: 4.0; IQR: 3–5) towards ASP. Job status and dispensing antibiotics without prescription were significantly associated with practice, while age and job status were associated with perception towards ASP. Conclusion: Community pharmacists demonstrated good practices and positive perceptions towards ASP. However, lack of training and lack of cooperation from prescribers limit their involvement in the program. Training of community pharmacists in antimicrobial stewardship and inter- professional collaboration are recommended.